EFFECT OF DILUENTS ON THE POROUS STRUCTURE OF CROSS-LINKED POLY(METHYL METHACRYLATE) BEADS - KUCUK, I; KUYULU, A; OKAY, O (SPRINGER VERLAG, 1995)
Copolymer beads based on methyl methacrylate (MMA) and ethylene glycol dimethacrylate (EGDM) were prepared by suspension polymerization technique. Two different solvents, namely toluene and cyclohexane, were used as the diluents in the polymerization system. It was found that toluene produces pores of radii 2 to 10 nm corresponding to the interstices between the nuclei. In the case of cyclohexane as the diluent, formation of large pores with a broad size distribution from 10 to 1000 nm were observed. These sizes correspond to the spaces between the microspheres and the aggregates forming the copolymer beads. The results indicate that, as in porous styrene - divinylbenzene copolymers, the solvating power of the diluent present during the network formation is mainly responsible for the structural characteristics of porous MMA/EGDM copolymer beads.
Keywords: STYRENE-DIVINYLBENZENE COPOLYMERS; 2-VINYLPYRIDINE; NETWORKS; Polymer Science